Women’s Financial Empowerment through Microfinance in Nepal: Evidence from Regression Analysis - Sunar, Upendra; Rawat, Baburam (Brixton Scholarly Review, 2026)
Women’s financial empowerment is an important dimension of inclusive growth, but the empirical evidence on the determinants of women’s financial empowerment in the context of the developing world remains scarce. The present study attempts to examine the determinants of women’s financial empowerment in the context of the women beneficiaries of microfinance services in Nepal. The primary data were collected from 400 women beneficiaries of some microfinance organizations in Nepal through the structured questionnaire method. The study applied various statistical tools, i.e., descriptive statistics, correlation analysis, and regression analysis, to examine the relationship between women’s financial empowerment and various socio-economic variables. The findings of the study suggest that decision-making power is the most important factor in women’s financial empowerment, followed by asset ownership, as these two variables are highly correlated with women’s financial empowerment at 0.352 and 0.319, respectively. On the other hand, family support, income, and education are the other important determinants of women’s financial empowerment, as these variables are highly correlated with women’s financial empowerment at 0.231, 0.176, and 0.084, respectively. The study also found that the regression analysis explains 61.2 percent of the variation in women’s financial empowerment, as the R² value is 0.612 in the present study. In line with the broader literature on financial inclusion, the study proposes that the addition of non-financial services such as financial literacy and advisory services can potentially improve empowerment outcomes. The results are useful for microfinance institutions, cooperatives, and development agencies aiming at promoting women’s financial empowerment in developing countries.